Insights on mother’s subjective well-being: The influence of emotion regulation, mindfulness, and gratitude - Warsah, Idi; Chamami, M. Rikza; Prastuti, Endang; Morganna, Ruly; Iqbal, Mirza Muchammad (Psikohumaniora: Jurnal Penelitian Psikologi, 2023)
Adaptation theory explains that mothers’ subjective well-being (SWB) is determined by their abilities to adapt to challenging life events using coping mechanisms. The literature highlights three latent coping mechanism factors: emotional regulation, mindfulness, and gratitude. This study aims to build a model of mothers’ SWB based on these factors. The sample comprised 302 young mothers (20-25 years old) selected using convenience sampling. Data were solicited from Likert scales that measured emotion regulation, mindfulness, gratitude, and SWB and analyzed using structural equation modeling. The results show that the SWB model had adequate goodness of fit, with a chi-square of 153.553 (p < .05), GFI of .934, AGFI of .899, CFI of .929, TLI of .906, and RMSEA of .076. The model shows that emotion regulation and mindfulness, mediated by gratitude, influenced SWB, with gratitude as a strong predictor of SWB. As an implication in counseling, gratitude interventions should be applied in practice.